Heteroepitaxial (111) ZnGa2O4 Thin Films Grown on (00.1) Sapphire by Pulsed Laser Deposition. Issue 9 (1st July 2020) - Luo, Sijun; Harrington, George F.; Wu, Kuan-Ting; Lippert, Thomas
Abstract : Heteroepitaxial ZnGa2 O4 thin films grown on sapphire substrates would be preferable for fundamental studies on properties of this material for device applications. To achieve near‐stoichiometric ZnGa2 O4 epitaxial thin films by pulsed laser deposition (PLD), the severe loss of Zn must be overcome. Herein, the fabrication and characterization of epitaxial (111) ZnGa2 O4 thin films grown on (00.1) sapphire substrates by PLD using a Zn0.97 Ga0.03 O target are reported. A deposition temperature of 750 °C and a laser fluence of 3.5 J cm −2 are suitable for growing near‐stoichiometric ZnGa2 O4 film. The in‐plane orientation relationship is identified to be [ 1 ¯ 1 ¯ 2 ] ZnGa2 O4 //[11.0] Al2 O3 . A 14.2 nm thick (111) ZnGa2 O4 epitaxial thin film with a Zn/Ga atomic ratio of about 0.47 shows a narrow full width at half maximum value for the rocking curve of 0.1° and a direct optical bandgap of 4.9 eV. Abstract : Using an ultrahigh Zn content target in pulsed laser deposition is demonstrated to successfully achieve the heteroepitaxial growth of high‐quality near‐stoichiometric (111) ZnGa2 O4 thin film on (00.1) sapphire substrate. Herein, an insight into the fabrication and properties of heteroepitaxial ZnGa2 O4 thin films grown on sapphire substrates is provided in view of potential device applications.